2018
DOI: 10.1172/jci.insight.99096
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomics identifies trimethyllysine, a TMAO-producing nutrient precursor, as a predictor of incident cardiovascular disease risk

Abstract: Using an untargeted metabolomics approach in initial (N = 99 subjects) and replication cohorts (N = 1,162), we discovered and structurally identified a plasma metabolite associated with cardiovascular disease (CVD) risks, N6,N6,N6-trimethyl-L-lysine (trimethyllysine, TML). Stable-isotope-dilution tandem mass spectrometry analyses of an independent validation cohort (N = 2,140) confirmed TML levels are independently associated with incident (3-year) major adverse cardiovascular event risks (hazards ratio [HR], … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 142 publications
(128 citation statements)
references
References 38 publications
6
118
3
1
Order By: Relevance
“…Interestingly, we observed a correlation ( r = 0.44) between TML and the gut microbial metabolite of carnitine trimethylamine‐N‐oxide (TMAO), which has been linked to cardiovascular diseases . The effects of TML on health and aging are poorly documented, with the notable exception of a recent untargeted metabolomics study reporting an association of TML with increased risk of cardiovascular diseases …”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, we observed a correlation ( r = 0.44) between TML and the gut microbial metabolite of carnitine trimethylamine‐N‐oxide (TMAO), which has been linked to cardiovascular diseases . The effects of TML on health and aging are poorly documented, with the notable exception of a recent untargeted metabolomics study reporting an association of TML with increased risk of cardiovascular diseases …”
Section: Discussionmentioning
confidence: 93%
“…1) [62]. Metabolomic studies suggested that high TMAO concentrations are positively correlated with cardiovascular events such as death, myocardial infarction (MI) and stroke [63]. In line with these data, in Apoe-deficient mice fed a TMAO-rich diet increased macrophage foam cell formation and aortic atherosclerotic plaque development was observed [28,64].…”
Section: Dietmentioning
confidence: 88%
“…It had been designated as a transporter of carnitine and of the (non-physiological) tetraethylammonium cation. However, in a really groundbreaking paper, Gründemann et al (130) recognised that the rates observed (using radioisotopes) were too small to be physiologically meaningful, and using a method that we would now refer to as 'untargeted metabolomics' (159)(160)(161)(162)(163)(164) , they incubated two kinds of HEK293 cells in serum. The first were normal cells, that, as with many transporters (119) , do not in fact express SLC22A4 at significant levels, while the second had been engineered to overexpress the transporter.…”
Section: Slc22a4: the Ergothioneine Transportermentioning
confidence: 99%